THE ANTIBACTERIAL POTENTIAL OF N-ACETYLCYSTEINE AS AN ENDODONTIC IRRIGANT ON THE CLINICAL ISOLATES OF THE ENTEROCOCCUS FAECALIS BIOFILM - Ridhalaksani, Ridzki; Nazar, Kamizar; Djauharie, Nila Kesuma; Meidyawati, Ratna; Npa, Dewa Ayu (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to evaluate the antibacterial potential of NAC as an endodontic irrigant on the clinical isolates of the Enterococcus faecalis biofilm. Methods: NAC with a pH of 2.5 and 11 (NAC pH 2.5 and NAC pH 11, respectively) were exposed to clinical isolates of E. faecalis biofilms for 1 min. The NAC samples were compared to 2% chlorhexidine (CHX), which is commonly used as an irrigant in persistent infections. The antibacterial potential of these irrigants was evaluated by comparing the bacterial count of the E. faecalis colonies after they were exposed to the irrigants. Results: The NAC pH 2.5 test group showed a reduction in the E. faecalis colonies, but this reduction was not statistically significant when compared to the 2% CHX group results. The NAC pH 11 test group showed the greatest reduction in bacterial colonies, and this reduction was statistically significant when compared to the NAC pH 2.5 and 2% CHX groups’ results. Conclusion: NAC pH 11 has antibacterial potential on the clinical isolates of E. faecalis biofilms.